The contribution of apprenticeship to the transition from education to employment - the position of the Labour Institute of the General Confederation of Greek Workers - Goulas, Christos; Karatrasoglou, Iakovos; Papageorgiou, Ira (Adult Education Critical Issues, 2026)
This paper examines the contribution of apprenticeship to the transition from education and training into employment, with a particular focus on the perspectives and policy proposals of the Labour Institute of the General Confederation of Greek Workers. In contemporary labour markets marked by technological change, demographic shifts, and evolving skill demands, young people face increasing difficulties securing stable and high-quality employment. Apprenticeship, as a structured form of work-based learning that combines classroom instruction with workplace experience, has emerged as a key mechanism for supporting smoother and more equitable school-to-work transitions. The study provides a historical overview of apprenticeship as a foundational mode of vocational learning and traces its evolution into modern systems integrated within national vocational education and training (VET) frameworks. It discusses the growing emphasis placed by European and international organisations on the development of high-quality apprenticeship systems and highlights the essential features of such systems, including strong labour-market relevance, clear regulatory frameworks, social dialogue, and meaningful pedagogical support. Quality assurance is presented as a continuous cycle requiring coordination, monitoring, and feedback to ensure that apprenticeship programmes meet learners’ needs and labour-market expectations. Focusing on Greece, the paper analyses the main apprenticeship schemes currently implemented in the country, outlining their structure, target groups, learning arrangements, and certification pathways. Despite significant progress and institutional improvements, challenges persist regarding programme quality, workplace conditions, supervision, and alignment with labour-market needs. In response, the Labour Institute proposes a comprehensive set of policy measures aimed at strengthening the governance, quality, and attractiveness of apprenticeship. These include establishing a registry of eligible companies, training workplace supervisors, enhancing social partner involvement, improving curriculum relevance, ensuring adequate compensation, and implementing robust monitoring and evaluation mechanisms. The paper concludes that high-quality apprenticeship is not only a tool for easing the transition to employment but also an essential component of a broader strategy for skills development, decent work, and inclusive economic growth.